Complement profiling for treatment outcomes in pulmonary TB - Pavan Kumar, Nathella; Nancy P., Arul; Hissar, Syed; Sivakumar, Shanmugam; Viswanathan, Vijay; Bethunaickan, Ramalingam; Kornfeld, Hardy; Babu, Subash (Frontiers in Immunology, 2026)
IntroductionThe complement system plays a vital role in the immune response against tuberculosis (TB), aiding in the recognition and clearance of Mycobacterium tuberculosis. However, its imbalance can result in either insufficient immune activation or excessive inflammation, both of which may contribute to poor treatment outcomes.MethodsThis study investigates whether baseline complement profiles are associated with unfavorable treatment responses in pulmonary TB patients. Using the Magpix multiplex cytokine assay, plasma levels of complement components (C2, C3, C3b/iC3b, C4, C4b, C5, C5a, C1q, MBL) and regulatory proteins (Factor B, Factor D, Factor H, Factor I) were measured in TB patients with poor treatment outcomes (n=68) and disease-free controls (n=108).ResultsAt both baseline (pre-treatment) and month two of anti-TB therapy, cases had significantly elevated levels of C3, C3b, C4b, C5, C5a, and C1q, and reduced levels of Factor B and Factor H compared to controls. Regression modelling revealed that C3, C3b, C4b, C5, C5a and C1q were associated with increased risk of unfavorable outcomes in unadjusted and adjusted analyses in the study cohort.DiscussionThese findings suggest that early and sustained complement activation, particularly through the classical pathway, is associated with adverse outcomes in TB. Complement dysregulation may thus serve as a potential prognostic marker for identifying individuals at risk of poor treatment response.